Can urban parks help with disaster risk reduction through educational awareness? A case study of Hurricane Harvey - Yıldırım, Yalçın; Keshavarzi G.; Aman A.R. (Elsevier Ltd, 2021)
This study examines the relationship between educational awareness and natural disasters through the lens of flood mitigation and also attempts to understand the perceptional and socio-demographical impacts in flood-prone areas. Recorded as one of the most catastrophic storms in the U.S., Hurricane Harvey caused massive damages to the environment and negatively affected public health and well-being. Having sustained three flood events since opening, including Hurricane Harvey, Buffalo Bayou Park in Houston, Texas, became the case study for this research as its role relative to educational awareness and natural disasters became the focus. The study performed a questionnaire-based survey with park users. Findings showed that concerns existed with respect to park use, socio-demographics, and accessibility. The findings also showed, however, that the park design contributed to flood mitigation strategies through establishment of educational awareness of natural disasters. This awareness was confirmed by park users being knowledgeable of some flood protection strategies, including planting native and local plants and curving the bayous naturally. Also, park users noted their preference for receiving disaster-related educational news via social media and partnerships/non-profit organizations. Finally, none of the socio-demographic features showed a difference for the logistic regression model as a significant predictor while attending educational events and residing within 20 min of the park significantly increased flood-mitigation awareness. This study highlights several efficient strategies that can complement the role of urban parks relative to how people experience and perceive educational activities concerning natural disasters.
Keywords: Disaster risk reduction; Educational awareness; Flood mitigation; Green spaces; Hurricane harvey